Development and evaluation of a normal phase liquid chromatographic method for the determination of tocopherols and tocotrienols in walnuts - Amaral, Joana S. (2008)
A high performance liquid chromatographic (HPLC) method for the determination of tocopherols and tocotrienols in walnut samples is described. The compounds were extracted with n-hexane, using a simple solid-liquid extraction procedure. Tocol was used as internal standard and BHT as anti-oxidant. The ehromatographic separation was achieved using an Inertsil 5 SI normal phase column operating with isocratic elution of n-hexane/1,4-dioxane (96.5:3.5, v/v), at a flow rate of 0.7 mL/min. The effluent was monitored by a series arrangement of a diodearray detector followed by a fluorescence detector. The detection limits were low, between 0.037 and 0.266 (jig/mL. The method was precise (% CV less than2.8%), accurate (% CV less than 5.6%), and, as a general rule, the recovery values were high (mean values ranging from 93.4% to 104%).